Human immunoglobulin from transchromosomic bovines hyperimmunized with SARS-CoV-2 spike antigen efficiently neutralizes viral variants - Zhuoming Liu; Hua Wu; Kristi A. Egland; Theron C. Gilliland; Matthew D. Dunn; Thomas C. Luke; Eddie J. Sullivan; William B. Klimstra; Christoph L. Bausch; Sean P. J. Whelan (Taylor & Francis Group, 2022)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) variants with amino-acid substitutions and deletions in spike protein (S) can reduce the effectiveness of monoclonal antibodies (mAbs) and may compromise immunity induced by vaccines. We report a polyclonal, fully human, anti-SARS-CoV-2 immunoglobulin produced in transchromosomic bovines (Tc-hIgG-SARS-CoV-2) hyperimmunized with two doses of plasmid DNA encoding the SARS-CoV-2 Wuhan strain S gene, followed by repeated immunization with S protein purified from insect cells. The resulting Tc-hIgG-SARS-CoV-2, termed SAB-185, efficiently neutralizes SARS-CoV-2, and vesicular stomatitis virus (VSV) SARS-CoV-2 chimeras in vitro. Neutralization potency was retained for S variants including S477N, E484K, and N501Y, substitutions present in recent variants of concern. In contrast to the ease of selection of escape variants with mAbs and convalescent human plasma, we were unable to isolate VSV-SARS-CoV-2 mutants resistant to Tc-hIgG-SARS-CoV-2 neutralization. This fully human immunoglobulin that potently inhibits SARS-CoV-2 infection may provide an effective therapeutic to combat COVID-19.